U.S. Indo pacific policy: Response of regional states - Khushboo Ejaz; Prof. Dr. Umbreen Javaid (Journal of Political Studies, 2018)
The downfall of American hegemony, the rise of China and India‟s economic power in the world has drastically increased the significance of Indo -Pacific region. This region has become the center of gravity of world‟s politics and economy. China as an emerging power is a threat to the U.S. hegemony and for India as well. The research is conducted to know the growing geostrategic and geopolitical importance of Indo - Pacific region for U.S and how it is changing dynamically. The study also shows the role of India in Asia-Pacific region, China‟s rising power and its status in the changings of geopolitics of Asia Pacific region and U.S. response towards the growing significance of China. In this contemporary era, the world is gradually diverted its attention from Euro Atlantic to Asia-Pacific region due to which Asia Pacific region is going to face enormous challenges, opportunities and threats from regional and extra regional states.